Humour as a Reflection of Linguistic Intelligence in the Indonesian Language within the Islamic Cultural Context - Yuwana, Rawuh Yuda (Universitas Islam Negeri Sunan Kalijaga, 2024)
This study delves into the intricate interplay of humour, psycholinguistics, morphology, themes, rema, and language intelligence in the Indonesian language context. Employing a detailed analysis of seven humorous texts, the research dissects linguistic constructs that emphasize abrupt contextual shifts and cognitive disruptions as the core of Indonesian humour. By investigating the strategic use of themes and rhema, this study reveals how humour often arises from semantic illusions, morphological play, and phonological ambiguity that challenge the reader’s expectations. Through a psycholinguistic lens, it highlights the cognitive processes involved in humour comprehension, demonstrating the pivotal role of language intelligence in detecting and appreciating linguistic incongruities. Additionally, the study connects these humorous strategies to broader Islamic cultural values, such as adab (etiquette), ikhlas (sincerity), hikmah (wisdom), and amanah (moral responsibility), showing how humour reflects ethical communication embedded within Islamic civilisation. The research concludes that humour in Indonesian is a linguistic phenomenon and a reflection of cultural and spiritual intelligence, emphasising how language structure and religious values converge in crafting and appreciating comedic expression